Managing the risk from children's travel cups. Issue 5 (4th January 2021) - Cameron, Alice; Colbert, Serryth Dominic; Macleod, Alisdair; Gill, Harinderjit S
Abstract : Introduction: UK national newspapers have reported cases of children (and adults) who have got their tongue trapped in a Disney travel mug lid, causing extreme distress to the patients, their parents and ED staff. Potential risks include oral endotracheal intubation necessitating emergency tracheostomy to secure the airway, tongue necrosis and dental trauma. Although Disney has withdrawn their original mug from the global market, the same dangers can occur with other internationally available brands. Our aim was to design, test and present an alternative lid. Methods and materials: We designed an alternative lid to fit onto the original Disney mug; our addition of two parallel bars prevented tongue protrusion into the lid. Prototypes of the original and new lids were three-dimensional printed for testing. A tongue substitute was developed and a representative 0.2 bar suction force was generated. The bottle was mounted in a material test machine, attached to the load cell fixture. Four samples each for the existing and new design were tested. The data were analysed by a custom Matlab script to extract the maximum force required to remove the tongues from the cup. Results: The new design resulted in a significant (p=0.0286, Mann-Whitney U) reduction in pullout force. For the existing design, the median pullout force was 4.64 N (minimum 3.86 N, maximum 4.91 N), while it was 2.37 N (minimum 2.20 N, maximum 2.53 N) for the new design. Trauma to the materials used with the original lid design was evident but not observed with our design. Conclusion: Our lid appears to offer a safer design that can avoid injuries. However, absolute safety remains unproved, as testing did not account for other body parts which may get trapped in the lid, nor did we test a range of tongue substitute sizes, and laboratory testing only was completed.